An evaluation of polymer composites for car bumper beam. (2017) - Osokoya, Olumide
Plastics were included in the array of automotive components materials in 1970s and today, they are the main materials for interior components of cars. Before then, traditional materials such as steel and iron were used for exteriors, interiors and structural parts. Modern technology reveals that plastics can be reinforced with certain materials to form new/novel materials called polymeric composites that can exhibit similar mechanical properties required for car structural components, such as metals. This is a major development and since legislations are getting stiffer concerning fuel consumption, the utilisation of lightweight components for cars are one of few logical measures of achieving standards. This article evaluates some polymer composites which are useful in replacing conventional materials for a car bumper beam, highlighting the fabrication methods of these composites and their properties to discuss the benefits of using them over conventional materials. The choice materials were compared using a material selection software, and the results show that carbon-fibre-epoxy composite has specific tensile strength which is about 360% greater than steel and 275% greater than aluminium. Also, glass-fibre-reinforced polypropylene composite and nylon-6-nanoclay nanocomposite, which have more competitive cost/kg of material, have as much specific tensile strength as steel and aluminium.